2012
DOI: 10.1111/j.1741-2358.2012.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional tooth units and nutritional status of older people in care homes in Indonesia

Abstract: This study revealed significant relationships between the number of FTUs and nutritional status. Keeping the posterior occlusion should be emphasized in order to maintain good nutritional status in older subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
(40 reference statements)
2
26
2
1
Order By: Relevance
“…Nearly half of our sample of LTC facility residents had 20 or more functioning teeth, which is lower than the prevalence reported from Qingdao, China, but higher than in Wales . Indeed, the prevalence of edentulous residents was low (<10%) compared to previous international studies of older people, but higher than in Southern Vietnam, where more participants aged 60 years or older had DMFT . The high prevalence and need for treatment of both coronal and root caries could be because new residents were admitted to the nursing homes with a compromised oral health status, or because they developed these oral diseases and conditions while living in the nursing homes.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Nearly half of our sample of LTC facility residents had 20 or more functioning teeth, which is lower than the prevalence reported from Qingdao, China, but higher than in Wales . Indeed, the prevalence of edentulous residents was low (<10%) compared to previous international studies of older people, but higher than in Southern Vietnam, where more participants aged 60 years or older had DMFT . The high prevalence and need for treatment of both coronal and root caries could be because new residents were admitted to the nursing homes with a compromised oral health status, or because they developed these oral diseases and conditions while living in the nursing homes.…”
Section: Discussioncontrasting
confidence: 65%
“…Periodontal disease increases with age; gingival recession and alveolar bone loss can occur due to traumatic tooth brushing, periodontal disease or periodontal treatment, which may lead to more tooth root surfaces with a risk of developing root caries . The mean numbers of teeth with coronal or root caries were much higher than in Indonesia, Thailand, Wales, Slovenia, Canada, or China, possibly because the number of participants with natural teeth was higher than in the other populations, despite the limited education of many of the older residents in our study.…”
Section: Discussioncontrasting
confidence: 63%
“…The proportion of people who were overweight (39.8%) and who had no posterior tooth pairs was lower than the results obtained in studies on the Indonesian population (46.8%) 23. Hilgert et al demonstrated that having no functional occluded tooth pairs or being edentulous increases the chance of being obese 24…”
Section: Discussionmentioning
confidence: 83%
“…This disease has spread considerably during the last few decades, especially among socioeconomically disadvantaged families (Allukian, ; American Academy of Pediatric Dentistry, ) and its impact on children's nutrition, growth, and development is often evoked in quality of life studies (Feitosa, Colares, & Pinkham, ; Schroth et al, ; Schroth, Levi, Kliewer, Friel, & Moffatt, ; Vania et al, ), but little is known about mastication in children with altered dentition. In adults, it was reported that any alteration of occlusal dental contacts may impact masticatory behavior and nutrition (Adiatman et al, ; Brodeur, Laurin, Vallee, & Lachapelle, ; Decerle, Nicolas, & Hennequin, ; Mishellany‐Dutour, Renaud, Peyron, Rimek, & Woda, ; Prakash, Kalavathy, Sridevi, & Premnath, ; Woda, Foster, Mishellany, & Peyron, ; Woda, Mishellany, & Peyron, ). The number of chewing cycles, the chewing duration and/or the chewing frequency are modified in such conditions (Decerle et al, ; Hennequin, Allison, Faulks, Orliaguet, & Feine, ; Peyron et al, ; van der Bilt, ).…”
Section: Introductionmentioning
confidence: 99%